Maternal Tn Immunization Attenuates Hyperoxia-Induced Lung Injury in Neonatal Rats Through Suppression of Oxidative Stress and Inflammation - Chen, Chung-Ming; Hwang, Jaulang; Chou, Hsiu-Chu (Frontiers in Immunology, 2019)
Hyperoxia therapy is often required to treat rat newborns with respiratory disorders. Prolonged hyperoxia exposure increases oxidative stress and arrests alveolar development in newborn rats. Tn antigen is N-acetylgalactosamine residue that is one of the most remarkable tumor-associated carbohydrate antigens. Tn immunization increases the serum anti-Tn antibody titers and attenuates hyperoxia-induced lung injury in adult mice. We hypothesized that maternal Tn immunizations would attenuate hyperoxia-induced lung injury through the suppression of oxidative stress in neonatal rats. Female Sprague–Dawley rats (6 weeks old) were intraperitoneally immunized five times with Tn (50 μg/dose) or carrier protein at biweekly intervals on 8, 6, 4, 2, and 0 weeks before the day of delivery. The pups were reared in room air (RA) or 2 weeks of 85% O2, creating the four study groups: carrier protein + RA, Tn vaccine + RA, carrier protein + O2, and Tn vaccine + O2. The lungs were excised for oxidative stress, cytokine, vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF) expression, and histological analysis on postnatal day 14. Blood was withdrawn from dams and rat pups to check anti-Tn antibody using western blot. We observed that neonatal hyperoxia exposure reduced the body weight, increased 8-hydroxy-2′-deoxyguanosine (8-OHdG) expression and lung cytokine (interleukin-4), increased mean linear intercept (MLI) values, and decreased vascular density and VEGF and PDGF-B expressions. By contrast, Tn immunization increased maternal and neonatal serum anti-Tn antibody titers on postnatal day 14, reduced MLI, and increased vascular density and VEGF and PDGF-B expressions to normoxic levels. Furthermore, the alleviation of lung injury was accompanied by a reduction in lung cytokine and 8-OHdG expression. Therefore, we propose that maternal Tn immunization attenuates hyperoxia-induced lung injury in neonatal rats through the suppression of oxidative stress and inflammation.